Espumas rígidas de poliuretano baseadas em óleos vegetais utilizando rejeitos industriais inorgânicos como carga e retardante de chamas - Virginia Ribeiro da Silva (2013)
Environmental issues related to industrial production, to a search for renewable products for the production of new materials, and recovery / recycling of waste have been subjects of several studies, both in science and in related areas. In this work are presented formulations for rigid polyurethane foams (PURF), using alternative and no petrochemical reactants. The foams were synthesized from vegetables based polyols (castor oil and tung oil based polyols), materials from renewable source, which showed a good alternative for the replacement of petrochemical polyols. Inorganic fillers, derived from industrial waste, have been added to rigid foam, with the intention of study applications for these residues and in an attempt to contribute to reducing the environmental impact caused by them. For the foams produced from polyol derived fromcastor oil, was used a black powder (reject P3) which is a waste from the Bayer process alumina production. This waste was characterized by various techniques and is rich in alumina (Al2O3) and aluminum hydroxide (Al(OH)3). Due to the high concentration of these two substances, this material has great potential as a flame retardant for foam. For the foams produced from tung oil based polyol, was used rice husk ash as the load. This is an industrial waste from the riceprocessing, rich in silica (SiO2), and also with flame retardance potential for the foam. The foams were characterized by FTIR, thermal analysis (TG, DTG and DTA) and SEM. Were also measured densities of materials and are performed mechanical, thermal conductivity and flame tests, to evaluate the load influence in the different foams properties.The results indicate that, for the loads percentages used, there were no morphological changes in the composites, compared to foam matrices. We observed an increment in the property of flame retardance and there was no significant loss of thermal properties. There are indications that there are secondary chemical interactions with the material waste P3 and the polyurethane synthesized castor oil based polyol. The same was not observed for the foams synthesized with tung oil based polyol, where rice husk ash as inorganic filler.